2018
DOI: 10.4066/biomedicalresearch.29-17-3854
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of antioxidant enzyme polymorphism in chronic obstructive pulmonary disease patients

Abstract: Background: Antioxidant system enzyme activity and polymorphism were investigated in Chronic Obstructive Pulmonary Disease (COPD), which is increasingly prevalent both in the world and our country. Methods: Malondialdehyde (MDA) was measured to determine lipid peroxidation, while Catalase (CAT), Paraoxonase (PON) and Superoxide Dismutase (SOD) enzyme activities were measured to determine antioxidant activity. For molecular analysis, leukocytes were separated and DNA was isolated from cell nuclei and the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…One study [28] was excluded because it included the same population as another study [29]. Finally, 12 studies were identified [13,14,[28][29][30][31][32][33][34][35][36][37]. Table 1 shows a summary of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study [28] was excluded because it included the same population as another study [29]. Finally, 12 studies were identified [13,14,[28][29][30][31][32][33][34][35][36][37]. Table 1 shows a summary of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 28 ] was excluded because it included the same population as another study [ 29 ]. Finally, 12 studies were identified [ 13 , 14 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation